Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pengurus (Studi Pada Pengurus Badan Eksekutif Mahasiswa FEB UNISMA) - Yasir Arafat; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Student organizations are a vehicle and a means of fostering students to increase knowledge and improve their intellectual and personal well-being in order to achieve university goals. One of the most important aspects of organizational life is the quality of leadership. Leadership has the responsibility to motivate members to achieve organizational goals, whereas leading an organization shows the relationship between leaders and members and how leaders lead their goals. This study aims to determine and measure the influence of leadership style, motivation and work discipline on the performance of BEM FEB UNISMA administrators. This research method uses quantitative methods with descriptive casual research. The population in this study is the administrators/members of the Student Executive Board of FEB UNISMA. In taking this sample using saturated sampling where all members of the population are used as samples. In this study, the sample was the entire management of the BEM FEB Islamic University of Malang for the 2020-2021 period consisting of the Daily Management Board, Internal Division, External Division, Talent Interest Division, Media Division, and Education Division, totaling 50 administrators. The results showed that leadership style, motivation and work discipline had a significant effect on the performance of the BEM FEM UNISMA management. Keywords: Management Performance, Leadership Style, Motivation, Work Discipline